Bioinspired Soft Microactuators. Issue 21 (16th April 2021) - Zhu, Pingan; Chen, Rifei; Zhou, Chunmei; Aizenberg, Michael; Aizenberg, Joanna; Wang, Liqiu
Abstract: Soft actuators have the potential of revolutionizing the field of robotics. However, it has been a long‐standing challenge to achieve simultaneously: i) miniaturization of soft actuators, ii) high contrast between materials properties at their "on" and "off" states, iii) significant actuation for high‐payload mechanical work, and iv) ability to perform diverse shape transformations. This challenge is addressed by synergistically utilizing structural concepts found in the dermis of sea cucumbers and the tendrils of climbing plants, together with microfluidic fabrication to create diatomite‐laden hygroscopically responsive fibers with a discontinuous ribbon of stiff, asymmetrically shaped, and hygroscopically inactive microparticles embedded inside. The microactuators can undergo various deformations and have very high property contrast ratios (20–850 for various mechanical characteristics of interest) between hydrated and dehydrated states. The resulting energy density, actuation strain, and actuation stress are shown to exceed those of natural muscle by ≈4, >2, and >30 times, respectively, and their weight‐lifting ratio is 2–3 orders of magnitude higher than the value of recent hygroscopic actuators. This work offers a new and general way to design and fabricate next‐generation soft microactuators, and thus advances the field of soft robotics by tailoring the structure and properties of deformable elements to suit a desired application. Abstract : Bioinspired soft microactuators (BSMAs) are designed with inspiration from the dermis of the sea cucumber and from plant tendrils, for simultaneous achievement of programmable actuation and high mechanical property contrast. Droplet microfluidics allows miniaturized, facile, and seamless fabrication of the BSMAs. Applications of the BSMAs as microlifters, reversible microgrippers, artificial tendrils, and microrobots for object manipulation/transportation in different and complex environments are demonstrated.